An experimental study on the influence of continuous ambient humidity conditions on relative humidity changes, chloride diffusion and microstructure in concrete. (1st November 2022) - Jin, Hesong; Fan, Xu; Li, Zhenlin; Zhang, Weizhuo; Liu, Jun; Zhong, Daojun; Tang, Luping
Abstract: Most engineering structures are exposed to various harsh environments, such as temperature fluctuations and humidity cycles, simultaneously. Additionally, moisture transfer and corrosive ion transport in concrete are driven by humidity gradients. Therefore, studying Chloride transport in concrete under constant humidity conditions is a meaningful research project. In this work, a new experimental setup was designed, and the Chloride diffusion behavior of concrete under a continuous humidity environment and NaCl immersion was investigated. Meanwhile, to accurately evaluate the internal humidity of concrete, humidity sensors were applied to the concrete. Additionally, the impacts of the water-binder ratio (w/b) and ambient humidity on the humidity diffusion coefficient, free Chloride content and bound Chloride content in concrete were evaluated. The microstructure was characterized by scanning electron microscopy, X-ray diffraction and mercury intrusion porosimetry. The results show that the content of free Chloride increases with an increasing w/b ratio. The humidity diffusion coefficient of concrete during water absorption (continuous high humidity environment) is significantly higher than that during water loss (continuous dry environment). Furthermore, under the drying condition, the Chloride content and the humidity diffusion coefficient on the concrete surface gradually increased, while during the wetting procedure, the Chloride content inside the concrete increased, and the humidity diffusion coefficient gradually decreased. However, the bound Chloride content inside the concrete is not affected by the humidity level in the environment. In the wetting environment, the calcium hydroxide in the matrix is gradually consumed, and the Chloride diffuses to the matrix to form more Friedel's salt and calcium carbonate. Moreover, lowering the w/b ratio or increasing the ambient humidity can enhance the formation of more hydrated compounds (C–S–H gel), which can reduce the total porosity and can also improve the ability of concrete to resist Chloride diffusion. Overall, this study provides a better understanding of and insight into the design and maintenance of seaside RC infrastructures. Highlights: An experimental method for the impact of moisture transport on chloride penetration in concrete. The moisture transport significantly increases the chloride penetration process in concrete. Moisture distribution in concrete changes with the vertical height or lateral depth from liquid level. Hysteresis time depended on humidity diffusivity, initial humidity difference in the concrete.